Avaliação tridimensional da linha de cimentação de pinos de fibra de vidro em função do preparo do conduto radicular e do tipo de cimento resinoso - Amanda Carolina Neiva Leijoto (2016)
Extensively destroyed and endodontically treated teeth require coronal restoration using prefabricated intraradicular fiber post or metal cast post. One cause of post failure is its loss of retention, causing detachment from the root canal. The discrepancy between the diameter of root canal and the post causes variation in the luting cement line, which determines different stress concentration inside the resin cement. Stress generated by polymerization shrinkage adversely affects the bond strength of the cement to dentin. The intraradicular canals can be prepared using conventional burs or using specific burs from the posts manufacturer. The study examined the adaptation of intraradicular fiberglass posts luted with two kinds of resin cements to root canals prepared with two types of burs. Twelve bovine incisor roots (length=15 mm, n=3) were prepared with different type of burs: Largo bur (Dentsply Maillefer, Ballaigues, Switzerland) or bur from White Post DC (FGM Produtos Odontológicos, Joinvile, Brazil). Two types of resin cement were used to cement the posts: Allcem (dual conventional resin cement - FGM Produtos Odontológicos, Joinvile, Brazil) and RelyX U200 (self-adhesive resin cement - 3M ESPE, St. Paul, USA). After posts cementations, the roots were stored in 100% humidity at room temperature for 7 days. Samples were scanned by computed microtomography (micro-CT). NRecon software was used to generate tridimensional images and CTan software analyzed the volume of cement (mm³) and porosity percentage (%) in the luting line. Additionally, the resin cements post-gel shrinkage (%) was measured by strain-gauge method (n=10). Roots prepared with Largo bur produced a significantly larger volume of cement (16.3 mm³, p<0.001) and significantly higher porosity percentage (39.1%) than those roots prepared with the specific bur (4,2 mm³ and 24,4%, respectively, p<0.001). Allcem resin cement presented higher percentage of porosity (34.1%) and higher post-gel shrinkage value (0.9%) when the results were compared to those of RelyX U200 (29.4% e 0.7%, respectively) (p<0,001). Thus, the use of specific bur for intracanal preparation and luting fiberglass post with RelyX U200 resin cement showed more favorable results regarding the evaluated properties.